2015
DOI: 10.2204/iodp.proc.347.101.2015
|View full text |Cite
|
Sign up to set email alerts
|

Expedition 347 summary

Abstract: Integrated Ocean Drilling Program Expedition 347 aimed to retrieve sediments from different settings of the Baltic Sea, encompassing the last interglacial-glacial cycle to address scientific questions along four main research themes: 1. Climate and sea level dynamics of marine isotope Stage (MIS) 5, including onsets and terminations; 2. Complexities of the latest glacial, MIS 4-MIS 2; 3. Glacial and Holocene (MIS 2-MIS 1) climate forcing; and 4. Deep biosphere in Baltic Sea Basin (BSB) sediments. These objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 98 publications
0
36
0
Order By: Relevance
“…F13). Although all physical property measurements described in "Physical properties" in the "Methods" chapter (Andrén et al, 2015a) were conducted for Site M0062, discrete P-wave and thermal conductivity data are too sparsely distributed to exhibit any discernable downcore trend. Noncontact electrical resistivity data also show little variability.…”
Section: Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…F13). Although all physical property measurements described in "Physical properties" in the "Methods" chapter (Andrén et al, 2015a) were conducted for Site M0062, discrete P-wave and thermal conductivity data are too sparsely distributed to exhibit any discernable downcore trend. Noncontact electrical resistivity data also show little variability.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Magnetic susceptibility measurements and rudimentary analyses of the natural remanent magnetization (NRM) were made on discrete specimens of known volume and mass (see "Paleomagnetism" in the "Methods" chapter [Andrén et al, 2015a]). A total of 290 discrete samples were taken from Holes M0062A (161 samples), M0062C (40 samples), and M0062D (89 samples) according to the site splice, with a higher density of samples taken in the upper 9 m. Magnetic susceptibility ranges between 0.07 × 10 -6 and 0.55 × 10 -6 m 3 /kg through the sequence, with the highest value found within Unit II, a well-sorted dark gray fine to medium sand.…”
Section: Paleomagnetismmentioning
confidence: 99%
“…To improve our understanding of the impact and magnitude of future environmental changes in the Baltic Sea region, it is essential to generate high-resolution paleoreconstructions in order to investigate how salinity and temperature varied in the past (e.g. Zillén et al, 2008;Andrén et al, 2015a;Ning et al, 2017). A multi-proxy approach, comprising proxies representative for bottom water, surface water, and air (terrestrial) conditions, is used here to reconstruct a wide array of environmental change (in particular temperature and salinity) from the same or closely neighbouring samples and thus how conditions simultaneously changed within the same age constraints.…”
Section: Introductionmentioning
confidence: 99%
“…No corrections were made within the Expedition DIS for this, with top and bottom depths of sections (in meters below seafloor) calculated on the basis of the core-top depth. However, the operations summary table (see T1 in the "Expedition 347 summary" chapter [Andrén et al, 2015]) shows adjusted recovery percentages for holes with >100% suggested recovery.…”
Section: Data Handling Database Structure and Accessmentioning
confidence: 99%
“…Methods for postexpedition research conducted on Expedition 347 samples and data will be described in individual scientific contributions published after the OSP. Detailed drilling and engineering operations are described in "Operations" within each site chapter and "Operational strategy" in the "Expedition 347 summary" chapter (Andrén et al, 2015). The information in this chapter will enable future identification of data and samples for further scientific investigation by interested parties.…”
Section: Introduction and Coringmentioning
confidence: 99%